Kenya agricultural withholding tax : Preliminary RIAPA analysis - International Food Policy Research Institute; Kenya Institute for Public Policy Research and Analysis; Mbuthia, Juneweenex; Omune, Lensa; Thurlow, James; Diao, Xinshen; Malot, Kenneth (International Food Policy Research Institute, 2024)
The slides were used by speakers of the workshop titled "Kenya Agricultural Withholding Tax" held last April 5, 2024 at KIPPRA offices, Nairobi, Kenya, organized by Kenya Institute for Public Policy and Analysis (KIPPRA) and CGIAR Research Initiative on National Policies & Strategies.